A survey of knowledge in the case management of acute respiratory infections (ARI) in children under the age of 5 years, amongst doctors and clinical nurse practitioners (CNPS) in the Khayelitsha district of Western Cape Province - Opedun, David (Department of Paediatrics and Child Health, 2018)
OBJECTIVE: To assess the knowledge of Doctors and Clinical Nurse Practitioners (CNPs) with regard to the case management of ARI in children under the age of 5 years in the Khayelitsha District of Western Cape Province. METHODS: The study was a descriptive survey of all the doctors and CNPs in Khayelitsha district. A questionnaire with closed and open-ended questions was self-administered. The international WHO case management guidelines were used as the gold standard except where the Paediatric Handbook was used as the reference with respect to questions on tuberculosis, bronchiolitis and croup. A comparative analysis was carried out on the knowledge scores of the doctors in the public sector, the private General Practitioners (GPs) and the CNPs. Correlation between years of experience and scores were measured. A further comparison was performed between doctors with and those without a post-graduate qualification in Paediatrics. The association of the use of WHO/ARI/90.5 manual and the Red books (University of Cape Town Paediatric handbooks) with the knowledge scores was also evaluated. RESULTS: 34 Doctors and 34 CNPs participated in the study. All the questionnaires administered were returned - 100% response rate. The median percentage scores of the doctors and the CNPs were 68.5 % and 63.0% respectively, p = 0.007. Twenty six percent of CNPs scored less than 50%. The median scores of the doctors with and of those without a post-graduate qualification in Paediatrics were 78.5% and 67.0% respectively, p = 0.005. The median scores of the doctors in the public sector and the private GPs were 71.0% and 65.0% respectively, p = 0.03. The median scores of participants who had seen and made use of the WHO/ARI/90.5 manual and of those who had not were 68.5% and 66.5% respectively, p = 0.13. The median scores of participants who had seen and made use of the University of Cape Town Paediatric handbooks and of those who had not were 67.0% and 64.0%, respectively, p = 0.37. The rank correlation co-efficients of doctors' and CNPs' scores with years of experience were 0.26 (p = 0.13) and -0.01 (p = 0.94) respectively. CONCLUSIONS AND RECOMMENDATIONS: (i) There was a wide range in knowledge scores, with approximately one quater of CNPs scoring less than 50%. Training in management of ARI is therefore necessary. (ii) The poor correlation between years of experience and knowledge indicates that experience is not by itself associated with improvement in knowledge, and supports the need for a service - oriented training programme. (iii) The impact of the recommended training programmes should be evaluated using this study as a baseline for comparison. (iv) There is a need for similar Knowledge, Attitude and Practice (KAP) studies on ARI in other areas to inform local trainers and to enable prioritisation of training.